The first hall of fame : a study of the statues in the Forum Augustum - Geiger, Joseph (Mnemosyne, bibliotheca classica Batava. Supplementum ;, 2008)
This book identifies the Greek and roman backgrounds to and influences on Augustus' decision as well as his probable motives for setting up these statues. s deal with the structure of the Forum and its statues, and provide a detailed analysis of the list of men (and women) known to have been included and the crieteria for inclusion. the additions to the heroes between Augustus and Trajan and the later impact of this Gallery of Heroes are discussed.--Back cover.